AC impedance of LiNi₀.₇Co₀.₂Al₀.₁O₂ and LiCo0₂ at room temperature / Nur Saidah Mohamed - Mohamed, Nur Saidah (2013)
New materials based on LiCo02 with some nickel and aluminium atoms substituted for other metals has become increasingly popular in cathode materials for Li-ion batteries. The purpose was to investigate AC impedance study of LiCo02 and LiNio.7Coo.2Alo.1O2 by electrochemical impedance spectroscopy (EIS). EIS is employed to investigate the electrochemical properties of LiCo02 and LiNio.7Coo.2Alo.1O2 cathode material. The results are interpreted on finding the conductivities of each material for pure cathode material and composite material by plotting Nyquist plots. The comparison conductivity between LiCo02 and LiNio.7Coo.2Alo.1O2 for pure cathode material and composite material also has been investigated in this study. Results indicated that the conductivity of LiNio.7Coo.2Alo.1O2 material is higher than LiCo02 material and the conductivity of composite material higher than pure cathode material.